Kesulitan Memahami Konsep Akidah di Kalangan Siswa: Media Pembelajaran Islami Berbasis Animasi Sebagai Solusi Efektif dalam Menjelaskan Materi Abstrak - Ahmad Fauzi Hasibuan; Mhd Adi Wahana; Suhut Parlindungan Daulay; Nurul Zaman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the difficulties experienced by students in understanding abstract concepts in Islamic creed (akidah) and to evaluate the effectiveness of Islamic-based animation learning media as an innovative and interactive solution. The research employs a qualitative Classroom Action Research (CAR) approach, conducted in two learning cycles using observation, interviews, documentation, and questionnaires as data collection techniques. The implementation of Islamic animation learning media demonstrated a significant improvement in students’ conceptual comprehension. The results indicate that the average understanding score increased from 35.25% in the preliminary stage to 89.25% after the final cycle, showing a substantial rise in students’ achievement levels. In addition, students’ enthusiasm, motivation, and active participation in classroom activities increased markedly when learning materials were presented through animated visualization rather than conventional lecture-based instruction. Expert validation confirmed that the developed instructional media meets pedagogical, didactic, and visual quality standards, and responses from teachers and students revealed positive perceptions regarding the relevance and attractiveness of animation-based learning. The findings highlight that Islamic-based animation learning media serves as an effective educational tool capable of simplifying and concretizing abstract theological concepts, enabling learners to construct deeper understanding through visual and contextual illustration.Therefore,the study recommends the broader application of animation-based Islamic instructional media in akidah education to enhance comprehension, engagement, and learning outcomes in schools.